Application of computer vision in the detection of chilling injury in bananas - Hashim, Norhashila; Osman, Azizah; Janius, Rimfiel; Shitan, Mahendran; Abdul Rahman, Russly; Zude, Manuela (Universiti Putra Malaysia Press, 2013)
Bananas were chilled at 6Â°C and the appearance of brown spots when exposed to ambient air, a phenomenon known as chilling injury (CI), was detected using computer vision. The system consisted of a digital colour camera for acquiring images, an illumination set-up for uniform lighting, a computer for receiving, storing and displaying of images and software for analyzing the images. The RGB colour space values of the images were transformed into that of HSI colour space which is intuitive to human vision. Visual assessment of CI by means of a browning scale was used as a reference and correlation between this reference values and hue was investigated. Results of the computer vision study successfully demonstrate the potential of the system in substituting visual assessment in the evaluation of CI in bananas. The results indicate significant influence, at Î±=0.05, of treatment days and temperature on hue. A strong correlation was also found between hue and visual assessment with R>0.85.